The role of LH in follicle development: from physiology to new clinical implications - Maria Longo; Francesca Liuzzi; Serena De Carlini; Antonio La Marca (Reproductive Biology and Endocrinology)
Abstract The process of follicle development is closely regulated by two pituitary gonadotropins: follicle-stimulating hormone (FSH) and luteinizing hormone (LH). Traditionally, folliculogenesis is considered to be divided into a gonadotropin-independent phase and a gonadotropin-dependent phase. Despite this, recent evidence has demonstrated that functional LH receptors are expressed even in smaller follicles during the phase considered to be gonadotropin independent. Luteinizing hormone promotes androgen synthesis within ovarian follicles and seems to significantly contribute to accelerate and enhance the transition from the primordial to the antral stage of folliculogenesis. Thus, LH could play a fundamental role in determining the number of recruitable antral follicles, with a direct impact on the cyclic recruitment of follicles and reproductive potential. Common clinical conditions of pituitary suppression such as hypogonadotropic hypogonadism, other than pregnancy and combined oral contraceptive use, have been considered to analyze the effect of lower serum LH levels on the functional ovarian reserve. This review outlines recent findings on the mechanisms of human follicle development, based on human and animal models, with a direct focus on possible new clinical applications.